Validation of Two Nonlinear System Identification Techniques Using an Experimental Testbed. (2004) - Lenaerts, V.; Kerschen, G.; Golinval, J.-C.; Ruzzene, M.; Giorcelli, E.
Abstract : The identification of a nonlinear system is performed using experimental data and two different techniques, i.e. a method based on the Wavelet transform and the Restoring Force Surface method. Both techniques exploit the system free response and result in the estimation of linear and nonlinear physical parameters.